The LIN28/let-7 Pathway in Cancer - Balzeau, Julien; Menezes, Miriam R.; Cao, Siyu; Hagan, John P. (Frontiers in Genetics, 2017)
Among all tumor suppressor microRNAs, reduced let-7 expression occurs most frequently in cancer and often correlates with poor prognosis. Activation of either LIN28A or LIN28B, two highly related RNA binding proteins and proto-oncogenes, is responsible for the global post-transcriptional downregulation of the let-7 microRNA family observed in many cancers. Specifically, LIN28A binds the terminal loop of precursor let-7 and recruits the TUTase ZCCHC11 that polyuridates pre-let-7, thereby blocking microRNA biogenesis and tumor suppressor function. For LIN28B, the precise mechanism responsible for let-7 inhibition remains controversial. Functionally, the decrease in let-7 microRNAs leads to overexpression of their oncogenic targets such as MYC, RAS, HMGA2, BLIMP1 among others. Furthermore, mouse models demonstrate that ectopic LIN28 expression is sufficient to drive and/or accelerate tumorigenesis via a let-7 dependent mechanism. In this review, the LIN28/let-7 pathway is discussed, emphasizing its role in tumorigenesis, cancer stem cell biology, metabolomics, metastasis, and resistance to ionizing radiation and several chemotherapies. Also, emerging evidence will be presented suggesting that molecular targeting this pathway may provide therapeutic benefit in cancer.